Censorship detected in VN (Vietnam) - Voidly (2026)
CRITICAL severity censorship detected in Vietnam. Confidence: 70%. Data sourced from OONI.
Censorship Incident ID: VN-2026-0924
Keywords: censorship; VN; censorship; critical